Irrigated areas drive irrigation water withdrawals - Arnald Puy (Nature Portfolio, 2021)
The global water demands of irrigated agriculture are estimated through country surveys or through hydrological models, but both approaches are taxing. Here, the authors show that they can simply be estimated as a function of irrigated areas.